Choroid plexus epithelium and its role in neurological diseases - Liu, Ruizhen; Zhang, Zhiping; Chen, Yibing; Liao, Junbo; Wang, Yuchang; Liu, Jingping; Lin, Zhixiong; Xiao, Gelei (Frontiers in Molecular Neuroscience, 2022)
Choroid plexus epithelial cells can secrete cerebrospinal fluid into the ventricles, serving as the major structural basis of the selective barrier between the neurological system and blood in the brain. In fact, choroid plexus epithelial cells release the majority of cerebrospinal fluid, which is connected with particular ion channels in choroid plexus epithelial cells. Choroid plexus epithelial cells also produce and secrete a number of essential growth factors and peptides that help the injured cerebrovascular system heal. The pathophysiology of major neurodegenerative disorders like Alzheimer's disease, Parkinson's disease，as well as minor brain damage diseases like hydrocephalus, stroke is still unknown. Few studies have previously connected choroid plexus epithelial cells to the etiology of these serious brain disorders. Therefore, in the hopes of discovering novel treatment options for linked conditions, this review extensively analyzes the association between choroid plexus epithelial cells and the etiology of neurological diseases such as Alzheimer's disease and hydrocephalus. Finally, we review CPE based immunotherapy, choroid plexus cauterization, choroid plexus transplantation, and gene therapy.